Spatial mapping of violence notifications and prevalence among vulnerable age groups in Espírito Santo State, Brazil (Brazilian Journal of Health Research, 2025)
Introduction: The notification of violence cases is an important tool for monitoring trends and guiding public policies to address violence across different life cycles. Objective: To analyze the prevalence and spatial distribution of violence notifications in the municipalities of Espírito Santo among vulnerable age groups, from 2011 to 2021. Methods: This is a descriptive ecological study using data from the Information System for Notifiable Diseases (SINAN) from 2011 to 2021. Notification rates per 10,000 inhabitants were stratified by age group (0–9, 10–19, 20–59, ≥60 years) and analyzed using Bayesian smoothing, Moran’s Index, and thematic mapping. Results: The overall mean notification rate of violence was 14.05 per 10,000 inhabitants. Regarding age-specific prevalence, the highest mean notification rate was found among adolescents (29.02/10,000), followed by adults (16.39/10,000), children (10.98/10,000), and older adults (9.34/10,000). Conclusion: The findings highlight the need for targeted public policies, the strengthening of surveillance in priority municipalities, and the inclusion of violence-related topics in the training of health professionals.
Keywords: Violence; Epidemiology; Information Systems; Spatial analysis